Moderation of religion in the Fatwa of Majelis Ulama Indonesia about the Ethics of da’wah in the Digital Age - Widoyo, Agus Fatuh; Abduh, Muhammad; Amrie, M. Abduh; Islamy, Athoillah (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2023)
Purpose - The rampant da’wah content in social media that triggers social and national disintegration is a problem and a big task for the government and Muslims in Indonesia to prevent it. This study seeks to identify the values of moderation in the fatwa of the Majelis Ulama Indonesia of East Java Province Number—06 of 2022 concerning da’wah Ethics in the Digital Era.Method - This qualitative study uses a philosophical normative approach. The study's primary data used the fatwa document of the Majelis Ulama Indonesia, East Java Province Number—06 of 2022 concerning da’wah Ethics in the Digital Era. Indicators of religious moderation conceptualized by the Ministry of Religious Affairs of the Republic of Indonesia as the primary analysis theory. The documentation techniques used in collecting data in this study and the data analysis techniques used were data reduction, presentation, and verification.Results - This study concludes that there is a dimension of religious moderation in the fatwa of Majelis Ulama Indonesia of East Java Province Number—06 of 2022 concerning da’wah Ethics in the Digital Era, among others, the value of anti-radicalism in the prohibition of the delivery of provocative da’wah content, the value of tolerance in the recommendation of delivering pluralist da’wah content, the value of national commitment in the recommendation of delivering da’wah content that leads to compliance with the country's constitution, and the accommodating value of local wisdom in the recommendation of delivering da’wah content that maintains public conduciveness. Implications – This study shows that mainstreaming religious moderation in Indonesia can be internalized in religious social fatwas.Originality - This study shows that the four indicators of religious moderation in Indonesia (tolerance, anti-radicalism, national commitment, and accommodating to local wisdom) can be internalized in the digital media space's code of ethics for da’wah activities.***Tujuan - Maraknya konten dakwah di media sosial yang memicu disintegrasi sosial dan bangsa merupakan masalah dan tugas besar bagi pemerintah dan umat Islam di Indonesia untuk mencegahnya. Kajian ini berupaya mengidentifikasi nilai-nilai moderasi dalam fatwa Majelis Ulama Indonesia Provinsi Jawa Timur Nomor—06 Tahun 2022 tentang Etika Dakwah di Era Digital.Metode – Penelitian kualitatif ini menggunakan pendekatan filosofis normatif. Data primer penelitian ini menggunakan dokumen fatwa Majelis Ulama Indonesia Provinsi Jawa Timur Nomor—06 Tahun 2022 tentang Etika Dakwah di Era Digital. Indikator moderasi beragama dikonseptualisasikan oleh Kementerian Agama Republik Indonesia sebagai teori analisis utama. Teknik dokumentasi yang digunakan dalam mengumpulkan data dalam penelitian ini dan teknik analisis data yang digunakan adalah reduksi data, penyajian, dan verifikasi.Hasil - Penelitian ini menyimpulkan bahwa terdapat dimensi moderasi beragama dalam fatwa Majelis Ulama Indonesia Provinsi Jawa Timur Nomor—06 Tahun 2022 tentang Etika Dakwah di Era Digital antara lain nilai anti radikalisme dalam larangan penyampaian konten dakwah yang provokatif, nilai toleransi dalam rekomendasi penyampaian konten dakwah pluralis, nilai komitmen nasional dalam rekomendasi penyampaian konten dakwah yang mengarah pada kepatuhan terhadap konstitusi negara, dan akomodatif nilai kearifan lokal dalam rekomendasi penyampaian konten dakwah yang menjaga kondusifitas publik.Implikasi – Kajian ini menunjukkan bahwa pengarusutamaan moderasi beragama di Indonesia dapat terinternalisasi dalam fatwa-fatwa sosial keagamaan.Orisinalitas - Studi ini menunjukkan bahwa empat indikator moderasi beragama di Indonesia (toleransi, anti radikalisme, komitmen kebangsaan, dan akomodatif terhadap kearifan lokal) dapat diinternalisasikan dalam kode etik ruang media digital untuk kegiatan dakwah.